Impact of introducing an HIV-PCR test at birth to attendance at follow-up early infant diagnosis (EID) services for HIV-exposed infants in Cape Town - Dunning, Lorna (Department of Public Health and Family Medicine, 2017)
Introduction: PCR testing at birth ('birth-testing') is conditionally advised by new World Health Organization guidelines for rapid diagnosis of infants infected with HIV in utero. Prompt diagnosis and early introduction of antiretroviral therapy (ART) can dramatically reduce mortality in HIV-infected infants. However, a negative result at birth must be followed by engagement in subsequent routine early infant diagnosis (EID) services (recommended at 6-10 weeks of age) to rule out intra-partum infection. There are few data on the implementation of this approach in sub-Saharan Africa and whether birth-testing affects the uptake of subsequent routine EID testing is unknown. Methods: We conducted a retrospective cohort study using routine clinical and laboratory data from a large obstetric hospital in Cape Town. All infants suspected to be at high risk of HIV-transmission, underwent birthtesting between July 2013-August 2015. Infants with a negative birth-test were matched to HIV-exposed infants who did not receive birth-testing. Maternal antenatal and obstetric characteristics of neonates were abstracted via folder review. Primary outcome was any subsequent HIV-PCR test before the end of follow-up, ascertained from the National Health Laboratory Service database. Data were analyzed using logistic regression models, examining independent predictors of presentation at follow-up EID testing. Results: Overall, 575 neonates underwent birth-testing, with 22 positive (3.8%) and 551 negative results. At follow-up EID presentation (n=871), 4 infected infants were identified (0.4%). Fewer infants who underwent birth-testing presented for later EID compared to infants who did not receive a birth-test (73% vs 85%), (Odds Ratio, 0.46; 95% confidence interval, 0.34-0.62). Infants who underwent birth-testing, also presented for later EID at a significantly older age (mean age 60 days vs.50 days, p<0.001). The significantly lower rate of EID presentation among birth-tested children persisted in multivariable analyses adjusting for maternal age, nadir CD4 cell count, ART use during pregnancy, gestation, infant sex, birthweight and infant feeding modality (Adjusted odds ratio, 0.60 95% confidence interval, 0.40-0.88). Conclusions: Neonates undergoing HIV testing at birth may be less likely to present for subsequent EID testing than those not birth-tested. Emphasis must be placed on appropriate counseling provided to caregivers on the need for further HIV testing after negative birth-test results.